Gestión del Talento Humano del GAD Parroquial Rural de La Unión de la ciudad de Babahoyo - Delacruz Santana, Nancy Mariuxi (2020)
The present case study is proposed through the management of human talent within the Decentralized Rural Parish Autonomous Government of the Union, which is a public institution in charge of planning, organizing, directing and controlling projects for the improvement of the Parish. . Attaching as a problem the mismanagement of human talent within the GAD: which welcomes delays in activities, the lack of commitment of workers, and at the same time in deterioration of communication to carry out the assigned work. In this way, this case study is focused on determining the causes that give rise to good management of human talent within the GAD, using as interview techniques an interview with the President of the Parish Board, a survey of other employees within the GAD, and the results of that show that if there is a poor execution of the projects, that it cannot be fully complied with because of the existing problems, therefore it cannot be achieved from the objectives set within the institution